PENDAMPINGAN DESAIN LOGO UNTUK PENINGKATAN VISUAL BRANDING DAN IDENTITY PRODUK UMKM PANJANG JIWO SURABAYA - Anggun Mizwa Anugerah; Nurkholish Majid (Universitas Merdeka Madiun, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the local economy; however, many still face challenges regarding visual branding and product identity. MSMEs in Panjang Jiwo, Surabaya, represent business actors who lack a strong logo and visual identity, leading to suboptimal brand image and product competitiveness. This assistance activity aims to enhance the understanding and capability of MSME owners in designing logos as a core element of visual branding and product identity. The implementation method includes observing MSME needs, discussing brand concepts, providing basic logo design training, and assisting in the design process and its application to promotional media and product packaging. The results indicate that the partner MSMEs successfully developed logos that represent the character, values, and uniqueness of their products visually. Furthermore, MSME owners gained increased knowledge regarding the importance of visual identity consistency in marketing. This logo design assistance is expected to strengthen brand image, increase consumer trust, and support the sustainability and development of MSMEs in Panjang Jiwo, Surabaya, amidst an increasingly competitive market.